Bodyspace : anthropometry, ergonomics and the design of work. - Pheasant, Stephen, ....-; Haslegrave, Christine M., ....- (Boca Raton : Taylor and Francis, 2006)
In the 20 years, since the publication of the first edition of "Bodyspace" the knowledge base upon which ergonomics rests has increased significantly. The need for an authoritative, contemporary and, above all, usable reference is therefore great. This third edition maintains the same content and structure as previous editions, but updates the material and references to reflect recent developments in the field. The book has been substantially revised to include new research and anthropometric surveys, the latest techniques, and changes in legislation that have taken place in recent years. New coverage in the third edition includes: Guidance on design strategies and practical advice on conducting trials; overview of recent advances in simulation and digital human modes; dynamic seating; recent work on hand/handle interface; computer input devices; laptop computer use and children's use of computers; design for an aging population and accessibility for people with disabilities; and; new approaches to risk management and new assessment tools, legislation, and standards. As the previous two editions have shown, "Bodyspace" is an example of the unusual: a text that is a favourite among academics and practitioners. Losing none of the features that made previous editions so popular, the author skilfully integrates new knowledge into the existing text without sacrificing the easily accessible style that makes this book unique. More than just a reference text, this authoritative book clearly delineates the field of ergonomics.
Keywords: Antropometrische ergonomie